A preliminary survey of chiropteran species caught in Balugo watershed, Salvacion, Tacloban City. - Mejica, Oliver George O.; Casas, Eulito Jr. V. (Tacloban City Oliver George O. Mejica, 2019)
The Philippines, a tropical country, is naturally rich and diverse in wildlife. Brgy. Salvacion, Tacloban City is a host of variety of species: birds, bats, reptiles and other wild animals. Situated in the said barangay is the Balugo Watershed which serves as a habitat for different kind of organisms. Thi study focuses on bats and its ecological role in the ecosystem. Bats eat flies, moths and other insects and thereby control insect populations very effectively. Some bats also serve as pollinators and seed dispersers of many plants that are important to humans. Bat populations are one of the best natural indicators of ecosystem health. The study aims to identify and characterize the Bat Species in Balugo Watershed, Salvacion, Tacloban City and to provide baseline information of bats in the area. Bats species were surveyed using 20mm mesh mist nets (3x8 meters) which were set 0-3 meters from the ground. These nets were placed on 5 different strategic locations along the flight path of the bats according to the locals. They were set up at dusk and taken down at sunrise. The captured bats were photographed and measured using a tape measure. Bar graphs were used to compare the sex, age, and number of bats caught per stations. Identification was done with the aid of the Key to the bats of the Philippines by Ingle and Heaney. The bats caught in the area were megachiropterans, or mega fruitbats. A total of 15 individuals were caught, belonging to two different species. The more abundant species was Rousettus amplexicaudatus with 10 individuals while Ptenochirus jagori has only 5 individuals. These findings will serve as a baseline data of the bats in the Balugo Watershed.
Undergraduate thesis (B.S. Biology) -- University of the Philippines, Tacloban.